Registration of systematic reviews in PROSPERO: 30,000 records and counting - Page, Matthew J; Shamseer, Larissa; Tricco, Andrea C (Université d'Ottawa | University of Ottawa, 2018)
Abstract Background The International Prospective Register of Systematic Reviews (PROSPERO) was launched in February 2011 to increase transparency of systematic reviews (SRs). There have been few investigations of the content and use of the database. We aimed to investigate the number of PROSPERO registrations from inception to 2017, and website usage in the last year. We also aimed to explore the epidemiological characteristics of and completeness of primary outcome pre-specification in a sample of PROSPERO records from 2017. Methods The PROSPERO database managers provided us with data on the annual and cumulative number of SR registrations up to October 10, 2017, and the number of visits to the PROSPERO website over the year preceding October 10, 2017. One author collected data on the focus of the SR (e.g. therapeutic, diagnostic), health area addressed, funding source and completeness of outcome pre-specification in a random sample of 150 records of SRs registered in PROSPERO between April 1, 2017 and September 30, 2017. Results As of October 10, 2017, there were 26,535 SRs registered in PROSPERO; guided by current monthly submission rates, we anticipate this figure will reach over 30,000 by the end of 2017. There has been a 10-fold increase in registrations, from 63 SRs per month in 2012 to 800 per month in 2017. In the year preceding October 10, 2017, the PROSPERO website received more than 1.75 million page views. In the random sample of 150 registered SRs, the majority were focused on a therapeutic question (78/150 [52%]), while only a few focused on a diagnostic/prognostic question (11/150 [7%]). The 150 registered SRs addressed 18 different health areas. Any information about the primary outcome other than the domain (e.g. timing, effect measures) was not pre-specified in 44/150 records (29%). Conclusions Registration of SRs in PROSPERO increased rapidly between 2011 and 2017, thus benefiting users of health evidence who want to know about ongoing SRs. Further work is needed to explore how closely published SRs adhere to the planned methods, whether greater pre-specification of outcomes prevents selective inclusion and reporting of study results, and whether registered SRs address necessary questions.